The Russia-Ukraine war reduced food production and exports with a disparate geographical impact worldwide - Nan Jia; Zilong Xia; Yinshuai Li; Xiang Yu; Xutong Wu; Yingjie Li; Rongfei Su; Mengting Wang; Ruishan Chen; Jianguo Liu (Communications Earth & Environment)
Abstract The transboundary impacts of regional war on global food trade remain underexplored, particularly regarding disruptions to production and trade networks. Here we address this gap by developing a rapid assessment framework that integrates remote sensing, policy monitoring, and network analysis to evaluate the effects of the Russia-Ukraine war on global winter cereal production and trade. Using satellite data, we estimated yield reductions for wheat, barley, and oats and analyzed the effects of export-ban policies enacted since February 24, 2022. Our findings indicate that lower- and middle-income countries were disproportionately impacted, as trade networks became fragmented, forming isolated clusters that threatened food accessibility. Geographically distant countries experienced greater disruptions than those near the conflict. This framework provides insights into the cascading effects of conflict on global food systems and offers a predictive tool for policymakers to address food availability challenges during future crises.